The role of zinc to mitigate heavy metals toxicity in crops - Hassan, Muhammad Umair; Nawaz, Muhammad; Mahmood, Athar; Shah, Anis Ali; Shah, Adnan Noor; Muhammad, Faran; Batool, Maria; Rasheed, Adnan; Jaremko, Mariusz; Abdelsalam, Nader R.; Hasan, Mohamed E.; Qari, Sameer H. (Frontiers in Environmental Science, 2022)
Heavy metals (HMs) contamination is serious concern across the globe and in recent time HMs intensity is significantly increased which is posing serious threat to crop growth and productivity. Heavy metals pose serious health issues in humans by entering in the human food chains. Therefore, it direly needed to reduce the effects of HMs on plants and humans by adapting appropriate practices. In this context application of micro-nutrients can be an important practice to mitigate the toxic effects of HMs. Zinc (Zn) is an important nutrient needed for plants growth and Zn application reduced the HMs induced toxicity in plants. Zn application reduced the HMs uptake by plant roots and their translocation to aerial plant parts which is considered as an important mechanism of HMs stress tolerance. Zn application also improves membrane stability, plant water relationship, nutrient uptake, photosynthetic performance, osmolytes accumulation, anti-oxidant activities, genes expression and brought favorable ultra-structural changes in plant body therefore, improve the plant performance under HMs stress. Zinc application substantially improves plant photosynthesis by improving synthesis of photosynthetic pigments, photo-system activities; enzymatic activities and maintaining structure of photosynthetic apparatus therefore ensure better growth under HMs stress. The beneficial role of Zn is related to higher accumulation of Zn in plants. Therefore, to enhance Zn accumulation in plants; the inherent potential of plants for Zn uptake must be improved. Moreover, application of Zn fertilizers is also a promising and quick solution to increase Zn accumulation to counter the effects of HMs. Therefore, Zn nutrition could improve the plant performance under HMs stress by modulating the plant physiological and biochemical functioning, antioxidant activities, osmolytes accumulation and genes expression. This review highlights potential mechanisms of Zn mediated HMs toxicity in plants and diverse strategies for increasing Zn induced benefits against HMs stress.